2009, No. 5, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Accounting theory and practiceDeimantė Kviklienė, Application of Generally Accepted Accounting Principles in the Baltic States, 7Kristina Rudžionienė, Changes of evaluation of financial statements‘ elements in Lithuanian accounting regulation of public sector, 15Kristina Rudžionienė, Inga Pečeliūnienė, Evaluation methods of financial statements‘ elements in Lithuanian accounting regulation of public sector, 25Kostas Valužis, Sąskaitų korespondencijų reikšmė ir netikslios teisės aktų formuluotės – žala valstybės ir jos piliečiams, 35Auditing theory and practiceDalia Daujotaitė, Performance audit in the public sector: theoretical dimension, 47Rasa Kanapickienė, Fraud risk management in process of internal control , 60Training of accounting specialistsGiedrė Balkytė, Milda Kvekšienė, Development of professional competencies of Accountancy and Finance study programmes students during the final internship, 67Gintarė Jakštonytė, Lukas Giriūnas, Evaluation of influence of the accountant’s professional image and prestige on the selection of accounting specialization at universities, 74Jadvyga Jurevičienė, Vilija Kolaitienė, The role of computerized accounting in the improvement of specialist training, 80Auksė Makšeckienė, The role of practical work experience in the study process, 87Romualdas Valkauskas, Training abilities of accounting specialists and economic statistics, 92Accounting abroadMindaugas Laurynaitis, Financial accounting regulation: German perspective, 99
Keywords: none